2003
DOI: 10.1097/00042737-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clarithromycin resistance and CYP2C19 genetic polymorphism on treatment efficacy of Helicobacter pylori infection with lansoprazole- or rabeprazole-based triple therapy in Japan

Abstract: The key to successful eradication of H. pylori, using lansoprazole or rabeprazole with clarithromycin and amoxicillin, is clarithromycin susceptibility, not CPY2C19 polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 46 publications
2
63
1
1
Order By: Relevance
“…[24][25][26][27][28] In Japan, standard rabeprazole dose is 10 mg 14 and most Japanese articles uses 10 mg b.i.d. for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27][28] In Japan, standard rabeprazole dose is 10 mg 14 and most Japanese articles uses 10 mg b.i.d. for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 No differences among CYP2C19 genetic polymorphism in our RAC are compatible with other previous study results. [24][25][26][27][28] In the direct comparison of LAC and RAC according to genotypic difference, the eradication rate of LAC in each genotypic polymorphism is statistically similar to that of RAC. The studies about pharmacokinetics and pharmacodynamics of both PPIs are like below; Mean 24-hour pH and percentage time for pH>4 were not significantly different between lansoprazole 30 mg and rabeprazole 20 mg in 72 healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the poorest eradication rate was found not in PMs, but in EMs. [5][6][7] All of our study-patients received omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs which are metabolized by CYP2C19 enzymes are cytostatics, proton pump inhibitors, antidepressants, sedative, beta blockers, antiviral and anti-fungal agents. [2][3][4][5][6][7][8][9] Recently, it was demonstrated that PMs of CYP2C19 showed a decrease in platelet responsiveness to clopidogrel. 10 In another study, it was reported that patients treated with antidepressants and genotyped as PMs for CYP2D6 and CYP2C19, remained in hospital for longer (median 57.5 versus 40.0 days) compared to IMs.…”
Section: Introductionmentioning
confidence: 99%